Ս. Ստեփանոս Նախավկան ԺԳ.-ԺԹ. դդ. հայկական կերպարուեստում - Աւետիսեան, Լիանա; Յովհաննիսեան, Կարէն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Св. Первомученик Стефан является одним из самых почитаемых святых заступников в армянской традиции наряду со Св. Георгием Просветителем. Образ Св. Стефана в армянской традиции имеет три тематических круга: избиение камнями, святой в деисусной композиции (заступник) и одиночный портрет с атрибутами. Согласно ранним письменным источникам (начиная с VI в.), его образ, в частности избиение камнями, изображался в армянских храмах. Но самая древняя роспись, датируемая 1297 годом и дошедшая до нашего времени, — это изображение избиения камнями, которое сохранилось в монастыре Дадиванк. Этот мотив, известный из фресок и рельефов, редко встречается в миниатюрах. Св. Стефан как святой заступник известен уже с VIII века в канонах литургических песнопений. В иконографии этот образ святого распространен как во фресках и миниатюрах, так и в рельефах, и даже в сравнительно поздних живописных работах. Главной особенностью иконографии Деисиса («заступничества») является то, что Св. Стефан в основном изображен вместе со Св. Иоанном Крестителем — святые заступаются за смертных перед Св. Богородицей с Младенцем (Христос Эммануиль). Одиночный портрет в основном встречается в hмаилах (магических свитках) 18—19-го вв., где святой изображен с своими атрибутами: одежда протодиакона (иногда епископа), кадило, ладанница и прочее. Тот же образ известен из кютахских изразцев монастыря Св. Иакова в Иерусалиме. Армянская иконография Св. Стефана соотносится с известными письменными и устными источниками о житии святого, начиная с Нового Завета. In the Armenian tradition, St. Stephen the Protomartyr, along with St. Gregory the Illuminator, is one of the most venerated intercessor saints. In the Armenian tradition, the image of St. Stephen has three thematic circles: the stoning, the saint in the Deesis composition and the solitary portrait with attributes. According to the earliest written sources (from the 6th century onwards), his image, in particular the stoning, was frequently depicted in Armenian monasteries. But the oldest wall-painting, dating back to 1297, which has survived to our days, is the depiction of stoning preserved in Dadivank. This motif, known from frescoes and reliefs, is rarely seen in miniatures. St. Stephan, as an intercessor saint, has been known since the 8th century in the canons of liturgical chants. In iconography, this image of the saint is common in both frescoes and miniatures, as well as in reliefs and even in relatively late pictorial works. The main feature of the iconography of Deesis (“intercession”) is that St. Stephen is mainly depicted together with St. John the Baptist. Both saints intercede on behalf of mortals before the Holy Mother of God with the Child (Christ Emmanuel). Single portraits are mainly found in hmayils (magical scrolls) of the 18th and 19th centuries, where the saint is depicted with all his attributes: garments of a protodeacon (sometimes of a bishop), censer, thurible, etc. The same manner of iconography is known from Kütahya pictorial tiles of St. James Church in Jerusalem. The Armenian iconography of St. Stephen correlates with the known written and oral sources on the life of the saint, beginning with the New Testament.
Keywords: Պատմություն